A5 ADMISSION AND RE-ADMISSION FOR UPPER GASTROINTESTINAL BLEEDING ARE MORE COMMON IN REGIONS UNDERREPRESENTED BY GASTROENTEROLOGISTS: A POPULATION BASED COHORT STUDY. (26th February 2020) - Charette, J H; Stach, J; Tanyingoh, D; Coward, S; Jelinski, S; Lang, E; van Zanten, S; Morrin, L; Reeb, L; Grigat, D; Hair, H; Novak, K L; et al.
Abstract: Background: Lack of access to gastroenterologists may influence outcomes for upper gastrointestinal bleeding (UGIB). Aims: To evaluate admission and re-admissions for patients with UGIB across the five health zones in Alberta that vary by access to local gastroenterologists. Methods: Administrative databases identified all patients presenting to an emergency department with an UGIB who were admitted to hospital in Alberta from 2010 to 2015 (n = 17143). Admissions were stratified based the patients' residence: Calgary, Edmonton, South, Central and North. Log-linear regression assessed an Average Annual Percentage Change (AAPC) in the incidence of UGIB hospitalizations with associated 95% confidence intervals (CI). Endoscopy and readmission to hospital within 30 days of discharge was evaluated. Results: The per capita number of gastroenterologists was highest in Calgary (3.9 per 100, 000) and Edmonton (3.8) as compared to Central (0.84), South (0.66), and North (0.41). Incidence of hospital admission for UGIB decreased in Alberta (AAPC=-6.9%; 95%CI: -8.4, -5.4); though rates for UGIB in Calgary and Edmonton was less common than non-metropolitan zones (Figure 1). Patients living in Calgary and Edmonton had lower 30-day hospital readmission rate (4.30% and 4.84%) as compared to North (11.95%), Central (10.74%), and South (8.24%) (Table 1). Patients in Calgary and Edmonton underwent endoscopic evaluation more frequently (79.6% and 76.1%) than the North, Central, and South (68.41%, 66.3%, and 71.36%). Conclusions: Patients presenting to emergency departments with UGIB were more likely to be admitted to hospital and subsequently be re-admitted within 30-days of discharge in regions underrepresented by gastroenterologists. Improving access to local gastroenterologists in may reduce the burden of hospitalizations for an UGIB. Funding Agencies: Partnership for Research and Innovation in the Health System (PRIHS) funded by Alberta Health Services and Alberta Innovates